2008
DOI: 10.1038/nature06992
|View full text |Cite
|
Sign up to set email alerts
|

Induced ncRNAs allosterically modify RNA-binding proteins in cis to inhibit transcription

Abstract: With the recent recognition of non-coding RNAs (ncRNAs) flanking many genes1-5, a central issue is to fully understand their potential roles in regulated gene transcription programs, possibly through different mechanisms6-12. Here, we report that an RNA-binding protein, TLS, serves as a key transcriptional regulatory sensor of DNA damage signals that, based on its allosteric modulation by RNA, specifically binds to and inhibits CBP/p300 HAT activities on a repressed gene target, cyclin D1 (CCND1). Recruitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
832
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 902 publications
(863 citation statements)
references
References 30 publications
16
832
2
1
Order By: Relevance
“…[6][7][8][9] FUS is a nucleoprotein that functions in DNA and RNA metabolism. 10 In this study, we found a large Japanese FALS family with mutations in the FUS gene with the characteristics of early onset. In addition, we report four mutations of the FUS gene in Japanese FALS.…”
mentioning
confidence: 83%
“…[6][7][8][9] FUS is a nucleoprotein that functions in DNA and RNA metabolism. 10 In this study, we found a large Japanese FALS family with mutations in the FUS gene with the characteristics of early onset. In addition, we report four mutations of the FUS gene in Japanese FALS.…”
mentioning
confidence: 83%
“…There is new evidence that TFs can interact directly with nascent RNA and recruit/inhibit chromatin modifying factors. 54 Wang et al recently showed that DNA damage leads to expression of non-coding RNA transcripts from the region upstream of the Ccnd1 promoter. The RNA binding protein, Translocated-in-Liposarcoma (TLS), binds to this nascent RNA and inhibits two histone acetyltransfeases leading to downregulation of the CCND1 mRNA.…”
Section: Possible Functions Of Divergent Rnasmentioning
confidence: 99%
“…Martianov et al 29) demonstrated that noncoding RNA could directly interact with the general transcription factor IIB and format a stable complex, which could dissociate the preinitiation complex and major promoter, thus decreasing dihydrofolate reductase gene expression. Wang et al 30) found that ncRNACCND1 could recruit an RNA-binding protein chain); (c) Intronic: stemming from the introns of the protein-coding genes; (d) Intergenic: located between two protein-coding genes [termed long intergenic noncoding RNAs (lincRNAs)]; and (e) Bidirectional: produced by the upstream sequence and the opposite direction of protein-coding genes 3,14) .…”
Section: Transcriptional Regulationmentioning
confidence: 99%